Diversity of blaPOM in carbapenem-resistant opportunistic pathogenic Pseudomonas otitidis in municipal wastewater - Doris Yoong Wen Di; Guangxiang Cao; Chuanqing Zhong; Tao Yan (IWA Publishing, 2023)
Metallo-β-lactamases (MBLs) encoding carbapenem resistance in wastewater are a well-known serious threat to human health. Twelve Pseudomonas otitidis isolates obtained from a municipal wastewater treatment plant (WWTP) in Hawaii were found to possess a subclass B3 MBL - POM (P. otitidis MBL), with a minimum inhibition concentration (MIC) range of 8-16 mg/L. The unrooted neighbor-joining phylogenetic tree showed that these blaPOM genes isolated in wastewater samples (n = 12) were distinctly different from other reference genes isolated from clinical, freshwater, animal, and soil samples except for isolates MR7, MR8, and MR11. MR7, MR8, and MR11 were found to have 4, 3, and 3 amino acid substitutions when compared to the type strain MC10330T and were closely clustered to the clinical reference genes. The meropenem hydrolysis experiment showed that isolates with multiple amino acid substitutions completely hydrolyzed 64 mg/L of meropenem in 7 h. The emergence of the opportunistic pathogen P. otitidis chromosomally encoding blaPOM in the treated municipal wastewater is an alarming call for the spread of this MBL in the environment. Further studies are required to understand the mechanism and regulation of this carbapenem-resistant β-lactamase in order to fill in the knowledge gap. HIGHLIGHTS Wastewater surveillance detected numerous carbapenem-resistant Pseudomonas otitidis isolates that showed minimum inhibition concentrations up to 16 mg/L of meropenem.; The blaPOM genes in the wastewater P. otitidis isolates possess mutations not observed previously in clinical and environmental sources.; Some wastewater P. otitidis isolates with multiple amino acid substitutions in the blaPOM gene catalyzed fast hydrolysis of carbapenem.;